Analisis Dimorfisme Kupu-Kupu Sayap Burung (Ornithoptera sp.) Endemik Papua - Evie L. Warikar; Euniche R.P.F. Ramandey; Hendra K. Maury (Jurnal Biologi Papua, 2019)
Ornitophera sp. is one of the groups of butterflies endemic in Papua and West Papua provinces. The significant morphological differences between male and female butterflies (dimorphism) are in the shape, size and color of the wings. Morphological characteristics are important sources of information. Based on the results of specimen collections at the Papua Insect Collection Laboratory (KSP) Jayapura, there are several species from various locations in Papua. The variation in dimorphism is likely to occur in this species which gives rise to new sub-species. The purpose of this study was to record the dimorphism of the endemic Bird Wing of Papua which had been stored in the Papua Insect Collection Laboratory (KSP) Jayapura. The method used is a direct measurement of the morphology of bird wing butterfly specimens stored in the KSP Laboratory, Cenderawasih University. Morphometric data were analyzed using the SPSS 20 and Multi Variate Statistical Package (MVSP 3.1) programs. The results obtained were 7 Ornithoptera species stored in the KSP Jayapura Laboratory, namely O. chiamera, O. goliath, O. meridionalis, O. paradisea, O. priamus, O. thitonus and O. rothschildi. Based on observations there are striking differences in color, shape and size between male and female in the same species.   Key words: birdwing butterfly, Ornithoptera sp., KSP Jayapura, dimorphisme.